Validity and Reliability of Knowledge and Behavioral Questionnaire about Weight Loss Diet in Teenage Girls - Amalia, Diva; Andayani, Tri Rejeki; Anantanyu, Sapja (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: The choice of diet method by teenage girl can be influenced by the knowledge. Methods: This study aimsto determining the validity and reliability of the knowledge and diet behavior questionnaire. The subject of this research is 30 female students. Data analysis of the validity using analysis of difficulty levels, differentiating power, distractor analysis, discrimination test and Lawshe’s Content Validity Ratio (CVR) analysis. The reliability test using Cronbach’s Alpha Coefficient test. Results: The results showed that 24 items of knowledge questions were declaired valid and 15 items in the diet behavior questionnaire were declared valid.The reliability test of the questionnaire for knowledge and diet behavior was declared reliable with result 0,877 and 0,858. Conclusions: The validity and reliability test of the instrument have proven that the instrument of diet knowledge and behavior has good validity and reliability values. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 133-138